Morphine analgesia and gastrointestinal morbidity in preterm infants: secondary results from the NEOPAIN trial. Issue 5 (18th December 2007) - Menon, G; Boyle, E M; Bergqvist, L L; McIntosh, N; Barton, B A; Anand, K J S
Abstract : Objective: To investigate the influence of morphine therapy and other factors on the attainment of full enteral feeds and on acquired gastrointestinal pathology in preterm infants. Design: Secondary data analysis from a randomised, placebo controlled trial. Setting: 16 neonatal intensive care units in USA, Sweden, France and UK. Patients: 898 infants (treatment group 449, control 449). Gestation (median (range)): 27 (23–32) weeks; birth weight (median (range)): 985 (420–2440) g. Interventions: Morphine (M) or placebo (Pl) given pre-emptively by intravenous loading dose (100 μg/kg of morphine) and infusion (10–30 μg/kg/h depending on gestation) while infants were ventilated, for up to 14 days. "Open-label" morphine (A) could be given if clinically indicated. Main outcome measures: Age at full enteral feeds and major acquired gastrointestinal pathology. Results: The group randomised to morphine was later in attaining full feeds (median days (quartiles): M 20 (13–29), Pl 17 (12–26); p = 0.003), and in starting feeds (median days (quartiles): M 5 (3–8), Pl 4 (2–7)). In a linear regression model, age at full feeds was independently associated with birth weight, a score of neonatal morbidities, neonatal dexamethasone use and cumulative morphine dose. There was no relationship between morphine use and acquired gastrointestinal pathology (M 9/449, Pl 8/449; χ 2 p = 0.81). Conclusions: Morphine delays the attainment of full enteral feeds, partly by delaying the start of feeding, but does not discernibly increase gastrointestinal complications. The attainment of full feeds is influenced by morphine dose, but other factors seem to be important, including birth weight and neonatal morbidity.